Chapter Narrative Approach in the Portfolio Method for Adult Education. Guidance for the Recognition of Competences in the Perspective of Lifelong Learning - DI RIENZO, Paolo (Studies on Adult Learning and Education, 2023)
The present paper is a contribution to the broad field of adult education within a lifelong learning perspective. It starts from literature and theories in this field, and develops a reflection based on empirical work, related in particular to the use of qualitative methodologies in the guidance process for adults engaged in the recognition of strategic competences acquired in non formal and informal learning contexts of civil service. The lifelong learning perspective places the valorisation of experience, reflective and transformative learning at the center to remove barriers that hinder adult participation. The outcome of this experimentation was the tutoring procedure to support reflexive and self-analysis activities for the construction of the competences portfolio.